Privacy Impact Assessments for Digital Repositories - Mhaidli, Abraham; Hemphill, Libby; Schaub, Florian; Cundiff, Jordan; Thomer, Andrea K. (International Journal of Digital Curation, 2022)
Trustworthy data repositories ensure the security of their collections. We argue they should also ensure the privacy of researcher and research subject data. We demonstrate the use of a privacy impact assessment (PIA) to evaluate potential privacy risks to researchers using the ICPSR’s Researcher Passport as a case study. We present our workflow and discuss potential privacy risks and mitigations for those risks. [A previous version of this article is available as an IDCC2020 Conference Paper]